الأسلوب التفسيري للشيخ محمد إدريس الكاندهلوي في تفسيره " معارف القرآن " : Sheikh Muhammad Idīrs Kandhalvī and His Approaches in Tafsīr Ma’ārif ul Qur'ān - Dr. Hafiz Haris Saleem (Al Basirah, 2022)
Muhammad Idīrs Kandhalvī is one of the most prominent and great scholars of the Islamic world. He is particularly known as a scholar of Qur'ān and Tafsīr in the Sub-continent. He has written many books in which the Ma’ārif al Qur'ān is very popular – A comprehensive exegesis of the Holy Qur'ān. This article carries out a comprehensive study of his Tafsīr; Ma’ārif al-Qur'ān and his methodology in his Tafsīr. The book is most celebrated Qur'ānic commentary in the Sub-continent. This article presents the methods, approach and worth of this book along with his biography. The method used in this research is descriptive and analytical. The study found that his writing style was unique and comprehensive. He has derived my solutions of contemporary issues from the perspective of the Holy Qur'ān. The study also recognized him as a socio- religious scholar for his time. At the end, the researcher has drawn some findings and conclusions.